Academic trajectory of a postgraduate student with autism spectrum disorder - Olivati, Ana Gabriela [UNESP]; Leite, Lúcia Pereira [UNESP] (Universidade Estadual de Maringa, 2017)
This study aims to delineate the academic trajectory and the social support perception of a postgraduate student with Autism Spectrum Disorder - ASD. The study was developed based on two procedures: (a) interview; (b) Social Support Perception Scale (SSPE) adapted to university context. Data collected in the interview were interpreted through verbal report analysis, for the establishment of meanings and senses attributed to certain phenomena. The average scores obtained with the SSPE were 1,78 (graduation) and 3,47 (post-graduation) for the practice support and 1,50 (graduation) and 3,20 (post-graduation) for the emotional support. Thematic axis obtained by the interview were: Graduation and Post-graduation Admission; Support core; Permanence in the University; Socio-emotional factors; Easinesses and difficulties encountered; Positive and negative aspects. It was possible to identify the absence of the social support perception during the graduation course and difficulties related to the learning and evaluation methods. On the other hand, in post-graduation, a higher level of social support perception and easinesses with academic skills was found, when compared to the graduation. However, in order to reach this level of education, students have to attend the undergraduate degree first, which is considered as a problematic instance in this research, because it meagerly responds to the differences.
Keywords: Autism; Colleges; School inclusion